2018
DOI: 10.3389/fimmu.2018.02014
|View full text |Cite
|
Sign up to set email alerts
|

The −3279C>A and −924A>G polymorphisms in the FOXP3 Gene Are Associated With Viral Load and Liver Enzyme Levels in Patients With Chronic Viral Liver Diseases

Abstract: The transcription factor FOXP3 is an essential marker of the development and activation of regulatory T cells (Tregs), which are cells specialized in the regulation and normal tolerance of the immune response. In the context of chronic viral liver diseases, Tregs participate in the maintenance of infections by promoting histopathological control and favor the immune escape of viral agents by suppressing the antiviral response. Single nucleotide polymorphisms (SNPs) may influence the function of FOXP3 in a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 85 publications
2
13
0
Order By: Relevance
“…It seems counterintuitive to associate an anti-in ammatory factor with the risk of tissue aggression; however, these ndings corroborate previous studies that suggest that variant T favors the persistence of viral infection in patients with brosis (10). With the increase in VL, there is a long-term pro-brogenic tendency induced by chronic in ammation and continuous response to healing (11), resulting in the uctuation of pre-cirrhotic biomarkers (12), such as GGT.…”
Section: Discussionsupporting
confidence: 82%
“…It seems counterintuitive to associate an anti-in ammatory factor with the risk of tissue aggression; however, these ndings corroborate previous studies that suggest that variant T favors the persistence of viral infection in patients with brosis (10). With the increase in VL, there is a long-term pro-brogenic tendency induced by chronic in ammation and continuous response to healing (11), resulting in the uctuation of pre-cirrhotic biomarkers (12), such as GGT.…”
Section: Discussionsupporting
confidence: 82%
“…Mutations in the FoxP3 gene, SNP-924 A > G, showed that G carrier status was associated with altered viral loads and liver enzyme levels in patients with chronic active hepatitis B (CHB-A) with inflammation and fibrosis. However, the frequencies of SNP-3279 C > A, A and-924 A > G, G were not directly associated with the histopathological profiles of the patients investigated [ 148 ]. It was also observed that the hepatic levels of mRNA expression of the NGF and p75NTR genes decreased and increased, respectively, in relation to the stage of inflammatory activity in HBV carriers.…”
Section: Hbv: the Impact Of The Geographical Area On The Prevalence Of The Virus In The Brazilian Amazonmentioning
confidence: 99%
“…Screening for inclusion was based on clinical and laboratory results as previously described (Pereira et al, 2018): Patients with persistent HBsAg for more than 6 months, positive or negative HBeAg, positive anti-HBeAg, and clinical and histological changes were included among patients with chronic hepatitis B (PCHB). Patients characterized by clinical and histological changes, variations in serum liver enzyme levels and positive viral load for Hepacivirus C were included in the group of patients with chronic hepatitis C (PCHC).…”
Section: Study Population and Ethical Aspectsmentioning
confidence: 99%
“…A control group (CG) of 300 blood donors from the Center for Hemotherapy and Hematology of Pará Foundation (HEMOPA), seronegative, and undetectable viral load for HBV, Hepacivirus C, and other agents typically screened in blood bank screening were determined. This group is specifically used to compare the genetic frequency of the studied polymorphisms (Pereira et al, 2018).…”
Section: Study Population and Ethical Aspectsmentioning
confidence: 99%